Strategi Komunikasi Pemasaran Produk Alutsista pada PT Bhinneka Dwi Persada - Trie Wulan Sari; Agustrijanto (UNIVERSITAS KALBIS, 2022)
The level of business competition is currently getting tighter, not least what occurs in the field of defense industry (INHAN) in the procurement of Main Tools Systems and Weapons (ALUTSISTA). PT Bhinneka Dwi Persada is a provider of goods and services. The purpose in this research is to find out how marketing communication strategies are carried out in marketing their products. Using descriptive qualitative research methods, researchers describe how marketing communication is carried out by PT Bhinneka Dwi Persada. Data collection techniques are observation, interviews, and documentation. The concepts used are the concept of Marketing Public Relations, the Concept of STP (Segmentation, Targeting, Positioning), and the marketing concept of AIDA. The results of this research marketing communication strategy conducted by PT Bhinneka Dwi Persada put forward the trust of prospective users and users, the application of the concept of marketing communication can be said to run well and effectively. This can be seen from the increase in sales activity from PT Bhinneka Dwi Persada.